2018
DOI: 10.1108/ijchm-12-2015-0722
|View full text |Cite
|
Sign up to set email alerts
|

Investigating antecedents and outcome of telepresence on a hotel’s website

Abstract: Purpose This study aims to investigate the relationships among sensory, emotional and cognitive attributes on a hotel’s website, customers’ telepresence, their attitudes toward the hotel’s website, brand attitudes and their behavioral intentions, based on telepresence and parasocial interaction theories as theoretical backgrounds. Design/methodology/approach A cross-sectional, online, self-administered survey was conducted to examine the proposed framework from previous hotel guests in the USA, who booked th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Interactivity is the most popular social feature of websites being studied, whereas customer relationship (Liu & Zhang, 2014) and cultural cues (Tigre Moura et al, 2015) have rarely been studied. Last, hedonic design refers to website attributes that trigger users' emotions and feelings (S. Lee, 2018). Three types of hedonic design features have been identified from the existing literature, including entertainment ( n = 11), innovative cues ( n = 4), and unpleasantness ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactivity is the most popular social feature of websites being studied, whereas customer relationship (Liu & Zhang, 2014) and cultural cues (Tigre Moura et al, 2015) have rarely been studied. Last, hedonic design refers to website attributes that trigger users' emotions and feelings (S. Lee, 2018). Three types of hedonic design features have been identified from the existing literature, including entertainment ( n = 11), innovative cues ( n = 4), and unpleasantness ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Emotional responses and perceptions have been relatively less explored. For instance, information quality, assurance, structure, and overall appearance of the website will affect users' adoption of the website for information search and purchases (e.g., Herrero & San Martín, 2012; H. Jeon et al, 2018; S. Lee, 2018). Whether the website can be personalized on the basis of users' preferences and contain entertaining features will also influence users' intention to revisit the website (e.g., Bilgihan et al, 2015; Bilgihan & Bujisic, 2015; M. M. Jeon & Jeong, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While lodging literature has previously linked behavioral intentions to several constructs (S. A. Lee, 2018;Park et al, 2019), scant research has examined consumers' sociability and behavioral intentions. Of the few studies that have researched such relationships, D.-H. Shin (2013) assessed how humans interact with social television systems and demonstrated that there is an indirect association between sociability and behavioral intentions through perceived usefulness, perceived ease of use, and attitude.…”
Section: The Effect Of Sociability On Booking Intentionsmentioning
confidence: 99%
“…In Ajzen and Fishbein’s (1969) behavioral intentions model, consumers’ attitudes resulting from their interactions with a product were shown to predict future behavior. While lodging literature has previously linked behavioral intentions to several constructs (S. A. Lee, 2018; Park et al, 2019), scant research has examined consumers’ sociability and behavioral intentions.…”
Section: Literature Reviewmentioning
confidence: 99%